PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK MELALUI PERMAINAN TREASURE HUNT PADA MATERI ANALISIS DATA DI KELAS VIII SMP - Gallih Maulana, Hans; Azhar Ahmad Smaragdina; Dion Dwi Rizky; Cindy Kusumawati; Febriansyah Satriagung Ganesha; Widyah Ayu Ningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study began with a problem found by researchers that is learning motivation in Informatics subjects. The observation’s results at SMP Negeri 29 Malang show learning motivation of 75% of students is less. This study’s purpose is improving the learning motivation of class VIII students at SMP Negeri 29 Malang by implementing the Treasure Hunt game on data analysis material. This game uses the unplugged method so that students find it easier to search for, analyze, and present data. This study uses the Kemmis and Taggart. Cycle starts from the planning, implementation, observation, and reflection repeatedly twice. The instruments used include observation sheets, questionnaires, and assessment. Treasure Hunt was tested on 20 students randomly. The results showed an increase in learning motivation, positive responses, and increase learning outcomes. Thus, the implementation of the Treasure Hunt game has effective in improving students' learning motivation.